Financial repression and the debt build-up in China: Is there a way out? - Miriam Campanella (European Centre for International Political Economy (ECIPE), 2016)
China's old recipe book for economic success, based on market distorting policies, is hindering the process toward a market-driven economy and the chance of being granted Market Economy Status (MES). The consequences of policy passivity may derail China into the middle income trap and pose severe uncertainty to global markets. As China's debt keeps mounting, particularly due to financial repression, mere domestic monetary reform may not be enough and may further harness the transition. Given China's fiscal and financial space, prudent fiscal policy, along with an acceleration in domestic economic reforms, can improve the social safety net, promote consumer confidence and spending and may be the most effective way to balance the China's economy and make its finances stable.
Keywords: 330; Öffentliche Schulden; Stabilisierungspolitik; China